A bivariate generating function for zeta values and related supercongruences. Issue 11 (1st December 2020) - Tauraso, Roberto
ABSTRACT: By using the Wilf–Zeilberger method, we prove a novel finite combinatorial identity related to a bivariate generating function for ζ ( 2 + r + 2 s ) . Such identity, which is an extension of a Bailey–Borwein–Bradley Apéry-like formula for even zeta values, is then applied to show several supercongruences.